Level Of Physical Activity (lpa) , Physical And Psychological Health Of School Adolescents - Chenafi , Miloud (sports creativity, 2025)
The objective of this research is to analyze the nature of the link between the level of physical activity (LPA) of schooled adolescents and their physical and psychological health, while knowing that despite the multiple benefits that result from a lifestyle active, several studies indicate a gradual decrease in practice during this age. To do this, we opted for the evaluation of the LPA through the 24h recall method, as well as the assessment of physical and psychological health by means of a questionnaire designed for this purpose. The study involved a sample of 120 students aged 15 to 18 years old who practice PSE. After the statistical analysis of the data collected, it was concluded that the level of physical activity (LPA) presented by the students is positively related to their physical and psychological well-being